2002
DOI: 10.2166/wst.2002.0321
|View full text |Cite
|
Sign up to set email alerts
|

Retention of granular sludge at high hydraulic loading rates in an anaerobic membrane bioreactor with immersed filtration

Abstract: This study shows the results of an Anaerobic Membrane Bioreactor with immersed filtration cartridges for granular biomass retention working at high hydraulic loading rates. Biomass retention capabilities, granular biomass structure and activity, filtration cartridges flux and organic material degradation performance were evaluated. Four reactors with a volume of 0.005 m3 were tested. Two different filtration cartridges were used (10 and 100 microm) with effective surface area of 0.05 m2. The filtration cartrid… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
6
0

Year Published

2003
2003
2022
2022

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(6 citation statements)
references
References 13 publications
0
6
0
Order By: Relevance
“…The production of soluble microbial products and the effect of these compounds on permeate flux in an AnMBR remains unclear. However, as suggested by Hernández et al (2002) , it is likely that an intermediate loading rate can maximize permeate flux in an AnMBR. They reported that permeate flux was greater at a medium loading rate (1.5 to 10 kg/m 3 ·d) than at a low loading rate (0.3 to 1 kg/m 3 ·d).…”
Section: Parameters Governing Permeate Flux In An Anaerobic Membrane mentioning
confidence: 96%
“…The production of soluble microbial products and the effect of these compounds on permeate flux in an AnMBR remains unclear. However, as suggested by Hernández et al (2002) , it is likely that an intermediate loading rate can maximize permeate flux in an AnMBR. They reported that permeate flux was greater at a medium loading rate (1.5 to 10 kg/m 3 ·d) than at a low loading rate (0.3 to 1 kg/m 3 ·d).…”
Section: Parameters Governing Permeate Flux In An Anaerobic Membrane mentioning
confidence: 96%
“…In an anaerobic membrane bioreactor with immersed filtration cartridges, retention of granular sludge at high hydraulic loading rates was studied. It showed that this kind of bioreactor maintained most of the advantages without biomass activity loss (Hernandez et al, 2002). Kang et al (2002) formation, backflushing and backfeeding effects were studied, and the differences between two types of membranes were explained by membrane morphology.…”
Section: Applications Andmentioning
confidence: 99%
“…Fouling due to EPS can also be considered a particular type of organic fouling. Generally, higher organic loading rates cause higher residual CODs and lower membrane fluxes [62]. It has been found that cases of inorganic fouling are dealt with less effectively than organic or biofouling [59].…”
Section: Fouling In Anmbrsmentioning
confidence: 99%